Identification and characterization of four PAX8 rare sequence variants (p.T225M, p.L233L, p.G336S and p.A439A) in patients with congenital hypothyroidism and dysgenetic thyroid glands - Esperante, Sebastian (2008)
Context: Thyroid dysgenesis may be associated with mutations in the paired box transcription factor 8 (PAX8) gene and is characterized by congenital hypothyroidism transmitted in an autosomal dominant mode. Objectives: The aim of this study was to identify new mutations in the PAX8 gene. Sixty congenital hypothyroidism-affected individuals with dysgenetic (agenesis, ectopia and hypoplasia) and eutopic thyroid glands were studied. Methods: The 12 exons of the PAX8 gene along with their exon-intron boundaries were amplified from genomic DNA and a mutational screening was performed by single-strand conformational polymorphism (SSCP) followed by direct sequencing of samples with abnormal migration patterns. The PAX8 mutations were functionally characterized by transient transfection experiments. Results: Molecular analysis of the PAX8 gene indicated that four affected individuals had four sequence differences: three novel variations [c.699C>T (p.L233L), c.1006G>A (p.G336S) and c.1317A>G (p.A439A)] and one recently reported [c.674C>T (p.T225M)], whereas the 56 remaining patients showed only wild-type alleles of PAX8. p.T225M, p.L233L and p.G336S variants were not detected in 530 chromosomes from 265 subjects randomly selected from the general population, whereas the p.A439A variant was identified in only one of the 530 chromosomes analysed. Functional analysis of the nonsynonymous substitutions showed that the p.T225M and p.G336S proteins had not lost their ability to bind a specific DNA sequence and to activate the transcription of the thyroglobulin (TG) promoter in synergy with thyroid transcription factor 1 (TTF1). Conclusions: We report the occurrence of two nonsynonymous substitutions, one recently reported (p.T225M) and one novel (p.G336S), and two novel synonymous substitutions (p.L233L and p.A439A) in the PAX8 gene. p.T225M and p.G336S are rare sequence variants or may act by inhibiting an unknown particular function. Our study also confirms the very low prevalence of PAX8 mutations in thyroid dysgenesis.